2015
DOI: 10.1371/journal.pone.0143231
|View full text |Cite
|
Sign up to set email alerts
|

Linear Growth and Fat and Lean Tissue Gain during Childhood: Associations with Cardiometabolic and Cognitive Outcomes in Adolescent Indian Children

Abstract: BackgroundWe aimed to determine how linear growth and fat and lean tissue gain during discrete age periods from birth to adolescence are related to adolescent cardiometabolic risk factors and cognitive ability.MethodsAdolescents born to mothers with normal glucose tolerance during pregnancy from an Indian birth cohort (N = 486, age 13.5 years) had detailed anthropometry and measurements of body fat (fat%), fasting plasma glucose, insulin and lipid concentrations, blood pressure and cognitive function. Insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 30 publications
3
32
0
Order By: Relevance
“…To our knowledge, no other cohort studies have examined the associations of directly assessed FM and FFM accretion during infancy with BC and cardiometabolic risk markers in early childhood. Using a 3-way conditional growth analysis of weight, height, and skinfolds to approximate fat and lean tissue gain in discrete age intervals from birth to 13.5 years, Krishnaveni et al [33] found that faster fat accretion from 5 to 9.5 years predicted higher fat percentage, waist–hip ratio, systolic blood pressure, insulin, and HOMA-IR at 13.5 years, but they reported no associations of fat or lean tissue at birth and growth over the periods 0–1 and 1–2 years with later BC or any of the studied cardiometabolic outcomes. In a small observational study, Koontz et al [48] found that accelerated FM accretion from 0 to 8 months of age was associated with an 8-fold increase in the odds of overweight/obesity at 9 years.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no other cohort studies have examined the associations of directly assessed FM and FFM accretion during infancy with BC and cardiometabolic risk markers in early childhood. Using a 3-way conditional growth analysis of weight, height, and skinfolds to approximate fat and lean tissue gain in discrete age intervals from birth to 13.5 years, Krishnaveni et al [33] found that faster fat accretion from 5 to 9.5 years predicted higher fat percentage, waist–hip ratio, systolic blood pressure, insulin, and HOMA-IR at 13.5 years, but they reported no associations of fat or lean tissue at birth and growth over the periods 0–1 and 1–2 years with later BC or any of the studied cardiometabolic outcomes. In a small observational study, Koontz et al [48] found that accelerated FM accretion from 0 to 8 months of age was associated with an 8-fold increase in the odds of overweight/obesity at 9 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, we acknowledge that conditional relative weight gain cannot differentiate between lean and fat gain. Very few birth cohorts have longitudinal measurements of lean and fat tissue through childhood, but recent data from a younger South Indian cohort has shown that the adipose component of childhood weight gain contributes most strongly to associations of weight gain with CVD risk markers 18 . A limitation of the study was cohort attrition, mainly because of deaths and out-migrations; of the original 10 691 live singleton births, we studied 1878 (18%).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to growth in childhood, school achievement and IQ are associated more strongly with early than with later growth in childhood. 21 , 22 , 23 , 24 , 25 , 26 In contrast, Krishnaveni et al 27 did not observe an association between linear growth in childhood and early adolescence and IQ in adolescence. Most of these studies relied on weight gain as the exposure variable, and until recently there was no attempt to disentangle the consequences of weight gain from those of linear growth.…”
mentioning
confidence: 88%